2007
DOI: 10.1177/153944920702700103
|View full text |Cite
|
Sign up to set email alerts
|

Community Participation and Life Satisfaction following Intensive, Community-Based Rehabilitation Using a Life Skills Training Approach

Abstract: This pilot study examined the effect of an intensive, community-based life skills training program on community integration and life satisfaction among individuals with traumatic brain injuries. Statistically significant improvements were found for subjects receiving intensive life skills training (n = 18) on two of three Community Integration Questionnaire subscales at the follow-up evaluation, whereas no changes were found for a group of community-dwelling, demographically matched control subjects (n = 18). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
6
2
2
Order By: Relevance
“…For youth at-risk due to problem behaviours, environmental stressors, or chronic health conditions, life skills are often taught through skill-based approaches such as the development of practical competencies in functional skills (e.g. selfcare and domestic skills) (Robertson et al 1998;Wheeler et al 2007); skills for independent living and transition (Cronin 1996;Healy & Rigby 1999;Evan et al 2006); and healthcare management including healthy living and preventative lifestyle choices (Christian & D'Auria 2006;Zoffmann & Lauritzen 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For youth at-risk due to problem behaviours, environmental stressors, or chronic health conditions, life skills are often taught through skill-based approaches such as the development of practical competencies in functional skills (e.g. selfcare and domestic skills) (Robertson et al 1998;Wheeler et al 2007); skills for independent living and transition (Cronin 1996;Healy & Rigby 1999;Evan et al 2006); and healthcare management including healthy living and preventative lifestyle choices (Christian & D'Auria 2006;Zoffmann & Lauritzen 2006).…”
Section: Introductionmentioning
confidence: 99%
“…; Wheeler et al . ); skills for independent living and transition (Cronin ; Healy & Rigby ; Evan et al . ); and healthcare management including healthy living and preventative lifestyle choices (Christian & D'Auria ; Zoffmann & Lauritzen ).…”
Section: Introductionmentioning
confidence: 99%
“…Such a relationship was not supported suggesting the need for a greater understanding of the concept of life satisfaction and the factors that influence it following TBI. Wheeler, et al (2007) did not find a significant increase in self-reported life satisfaction at 90-day follow-up despite increases in community integration as measured by the CIQ. In the current study, a significant decrease in life satisfaction was reported over this period followed by a return to baseline levels at one year.…”
Section: Satisfaction With Lifementioning
confidence: 66%
“…It is an extension of the work of Wheeler, et al, (2007) who studied the effectiveness of intensive, life skills training with individuals with severe TBI. Findings from that research supported the treatment approach to improve community integration.…”
Section: Introductionmentioning
confidence: 99%
“…Each group and each person has specific characteristics in the mean of occupation. Therefore, the occupational therapy assessment of the life skills is provided individually by employing the practical reference models either for general praxis, such as Model of Human Occupation (MOHO) [18,19], Person-Environment-Occupation Model (PEO) [20][21][22], and VdT Model of Creative Ability (MOCA) [23,24] or the ones that particularly developed for this use, such as Occupational Therapy Life Skills Curriculum Model [13], Life Skills Training Approach [25], and etc.…”
Section: Name Of the Instrument Validation Samplesmentioning
confidence: 99%